The Development of a Self-Awareness Skill for High School Students with the Process of Social and Emotional Learning - Supatarayan Thaintheerasombat,; Chowwalit Chookhampaeng, (Journal of Educational Issues, 2024)
The research purposes for encouraging study of social and emotion intelligence (S+EI) for secondary school students. Also, this research studied the developing aware of oneself and others in the present and utilising that awareness to manage oneself (our behaviour, our responses to difficult or demanding situations) and our relationships with others in deference age and gender to find the result of self-awareness between two groups of students including students who have learnt self-managing social and emotion and students who have studied in traditional way. The methodologies that used in this research are composed of the study plan that encourages development of intelligence for secondary school students by observing behaviour of both social and emotion, observing individual behaviour, and doing questionnaire about social and emotion by adopting statistic, frequency, and percentages to evaluate. The researcher found that students from Mahasarakham University Demonstration school (Secondary school) who have learnt to manage their social and emotion have different result of developing their social and emotion intelligence according to different study period, gender, and age. Therefore, students who have different learning styles had different self-awareness learning outcomes at the statistical significance level of .05.